Reproducibility of Heart Rate Variability Threshold in Untrained Individuals - Novelli, Fabiula Isoton; de Araújo, Jaqueline Alves; Tolazzi, Geovane José; Tricot, Gabriel Kolesny; Arsa, Gisela; Cambri, Lucieli Teresa (International Journal of Sports Medicine, 2019)
The aim of this study was to evaluate the reproducibility of the heart rate variability threshold (HRVT) by different HRV indexes and determination criteria. 68 untrained participants, 17 women (24.09±4.91 years old; 21.54±1.97 kg∙m−2) and 51 men (24.52±3.52 years old; 26.51±6.31 kg∙m−2), were evaluated on 2 different days (test and retest). The HRVT was determined during an incremental exercise test using 2 indexes (SD1 and RMSSD) and criteria (HRTV1, first intensity of physical effort with index<3 ms, and HRVT2, first intensity of physical effort, in which the index presents a difference<1 ms between 2 consecutive intensities). There was no significant difference (p<0.05) between the test and retest for any of the variables evaluated. All variables, except for the rate of perceived exertion at HRVT2, presented moderate to high intraclass correlation coefficient (HRVT1: 0.55–0.85 and HRVT2:0.58–0.69). All variables at HRVT1 and the heart rate at HRVT2 showed coefficient of variation ~ 10%. The HRVT, regardless of criteria and HRV index used, showed satisfactory reproducibility. Thus, these criteria can be used to assess clinically autonomic cardiac modulation and aerobic capacity, and to analyze the effect of different interventions.
Keywords: autonomic nervous system; physical training; physical fitness; anaerobic threshold; parasympathetic activity